Associations Between a Polymorphism in the Rat 5-HT1A Receptor Gene Promoter Region (rs198585630) and Cognitive Alterations Induced by Microwave Exposure - Li, Haijuan; Gao, Yu; Zou, Yong; Qiao, Simo; Zhi, Weijia; Ma, Lizhen; Xu, Xinping; Zhao, Xuelong; Zhang, Junhua; Wang, Lifeng; Hu, Xiangjun (Frontiers in Public Health, 2022)
The nervous system is a sensitive target of electromagnetic radiation (EMR). Chronic microwave exposure can induce cognitive deficits, and 5-HT system is involved in this effect. Genetic polymorphisms lead to individual differences. In this study, we evaluated whether the single-nucleotide polymorphism (SNP) rs198585630 of 5-HT1A receptor is associated with cognitive alterations in rats after microwave exposure with a frequency of 2.856 GHz and an average power density of 30 mW/cm2. Rats were exposed to microwaves for 6 min three times a week for up to 6 weeks. PC12 cells and 293T cells were exposed to microwaves for 5 min up to 3 times at 2 intervals of 5 min. Transcriptional activity of 5-HT1A receptor promoter containing rs198585630 C/T allele was determined in vitro. Electroencephalograms (EEGs), spatial learning and memory, and mRNA and protein expression of 5-HT1A receptor were evaluated in vivo. We demonstrated that transcriptional activity of 5-HT1A receptor promoter containing rs198585630 C allele was higher than that of 5-HT1A receptor promoter containing T allele. The transcriptional activity of 5-HT1A receptor promoter was stimulated by 30 mW/cm2 microwave exposure, and rs198585630 C allele was more sensitive to microwave exposure, as it showed stronger transcriptional activation. Rats carrying rs198585630 C allele exhibited increased mRNA and protein expression of 5-HT1A receptor and were more susceptible to 30 mW/cm2 microwave exposure, showing cognitive deficits and inhibition of brain electrical activity. These findings suggest SNP rs198585630 of the 5-HT1A receptor is an important target for further research exploring the mechanisms of hypersensitivity to microwave exposure.